Personal Selling And Service Relationship With Customer Loyalty In Ud. Successindo Bengkulu - Galuh Hardiyanti; Ida Anggriani; Nia Indriasari (BIMA Journal (Business, Management, & Accounting Journal), 2021)
The research aim to know the relationship of personal selling with customer loyalty at UD. Suksesindo Bengkulu and to know the relationship of service with customer loyalty at UD. Suksesindo Bengkulu. Method Analysis the used is correlation spearman rank and hypothesis test. From result of calculation of correlation of rank spearman between personal  selling with customer loyalty at UD Suksesindo Bengkulu known by value of rho count equal to 0,567 its meaning the relationship of personal selling with customer loyalty at UD Suksesindo Bengkulu is enought, because correlation value reside in  coefficient interval 0,400 - 0,599. From result of calculation of correlation of rank spearman between service with customer loyalty at UD Suksesindo Bengkulu known by value of rho count equal to 0,611 its meaning of the relationship service with customer loyalty at UD Suksesindo Bengkulu is strength, because correlation value reside in coefficient interval 0,600 - 0,799. Based on the hypothesis test, it is known that personal selling and service have a significant relationship with customer loyalty at UD. Suksesindo Bengkulu.